Clinicopathological Profile of Sinonasal Masses: A Hospital Based Study - Goswami, Rashmi Rekha; Deuri, Chigachi; Daimary, Michimi; Datta, Balmiki (Asian Pacific Journal of Cancer Care, 2025)
Objective: To analyze the clinicopathological spectrum of sinonasal masses, encompassing both neoplastic and non-neoplastic lesions, based on clinical, radiological, and histopathological findings. Methods: A retrospective study was conducted over a period of three years at Fakhruddin Ali Ahmed Medical College, Assam. A total of 50 patients presenting with sinonasal masses were evaluated. The assessment included clinical examination, radiological investigations, and histopathological evaluation, with immunohistochemistry applied in select cases for diagnostic confirmation. Results: Non-neoplastic lesions were the most common, with inflammatory polyps accounting for the majority. Among the neoplastic lesions, inverted papilloma was the most frequent benign tumour, while squamous cell carcinoma was the predominant malignant neoplasm. Conclusion: Sinonasal masses exhibit a wide pathological spectrum. Histopathological examination remains the gold standard for definitive diagnosis, with immunohistochemistry serving as a useful adjunct in certain cases.